2022
DOI: 10.1039/d1fo03899k
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and preventive effect on non-alcoholic fatty liver disease of oligosaccharides from Bletilla striata

Abstract: The structural characteristics of BOs were identified and their preventive effects were evaluated on NAFLD using an HFD-induced obese mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Physical activity has benefits in preventing metabolic syndrome (Montesi et al, 2013). Most studies have revealed benefits from changing lifestyles and herbal polysaccharides (Hu et al, 2022). The underlying mechanisms of polysaccharides affecting bacteria in the colon and bile acid metabolism have been shown in some articles (Hong et al, 2020; Zhong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has benefits in preventing metabolic syndrome (Montesi et al, 2013). Most studies have revealed benefits from changing lifestyles and herbal polysaccharides (Hu et al, 2022). The underlying mechanisms of polysaccharides affecting bacteria in the colon and bile acid metabolism have been shown in some articles (Hong et al, 2020; Zhong et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, oral drug administration exacerbates the metabolic burden in the liver, which might result in metabolic disturbances and thereby increasing the susceptibility to carcinogenesis [ 86 ]. Issues regarding hepatotoxicity have been resolved by the promoted liver regeneration by BT [ 87 ], PP [ 88 ], BD [ 89 ], CH [ 90 , 91 ], LC [ 92 , 93 ], SK [ 94 ], and CWT [ 95 ]. ③ IBD patients are susceptible to malnutrition including anemia, amino acid, and vitamin deficiency [ 96 ], which could be rescued by PP [ 97 ] due to its hematopoiesis-promoting effect [ 98 100 ] and by the addition of pearl that is produced from shellfish mollusks which contain 20 amino acids and Fe and Mg elements [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…BO was prepared according to the reference ( Hu et al., 2022 ). In brief, 1 g of BP was added to 100 mL distilled water and stirred at 90°C to dissolve.…”
Section: Methodsmentioning
confidence: 99%
“…Studies show that BP could be degraded to B. striata oligosaccharide (BO) with appropriate polymerization degree and low molecular weight by acid hydrolysis. And BO had a particular therapeutic effect on obesity and non-alcoholic fatty liver disease by regulating gut microbiota and their metabolites ( Hu et al, 2020 ; Hu et al., 2022 ). However, no studies show whether there are some differences in the prebiotic characteristics between BP and BO.…”
Section: Introductionmentioning
confidence: 99%